Novel approaches to evaluate sustainability of pasture-based livestock systems. (19th October 2016) - Bernués, A.
Abstract : Pasture-based livestock systems, often located in High Value Nature farmland areas, hold the greatest potential to deliver public goods across European agricultural systems. They play an important role in preserving agricultural landscapes, farmland biodiversity, cultural heritage, and in sustaining rural development. However, many of these functions are ignored in evaluation frameworks because public goods do not have market price and are often ignored in policy design, so farmers do not get the appropriate incentives to provide them. Different conceptual frameworks can be utilized to evaluate the multiple functions or services of these systems: Multifunctional Agriculture, Ecosystem Services, and Total Economic Value. We analyze the common characteristics of these concepts (e.g. they place human benefits and societal demands at the core of their definitions), their specificities (e.g. use of different units of analysis and spatial-temporal scales), and how they can be embedded in the wider concept of sustainability. Finally, we illustrate how the different concepts can be combined to evaluate pasture-based livestock farming systems from a socio-cultural and economic perspective. The public goods (ecosystem services) provided by representative case studies in Mediterranean and Nordic regions are quantified (also in monetary terms) under different environmental/policy scenarios. The results show that there is a clear underestimation of the socio-cultural and economic values of ecosystem services provided by these farming systems. They also show that the social welfare loss linked to further abandonment of livestock farming, and the associated environmental degradation, is very large. From a societal perspective, it is necessary to jointly measure the biophysical, socio-cultural and monetary values of ecosystem services (market and nonmarket) in order to promote the sustainability of pasture-based livestock systems.